Inhibition of interleukin‐1β signalling promotes atherosclerotic lesion remodelling in mice with inflammatory arthritis. Issue 11 (9th November 2020) - Dragoljevic, Dragana; Lee, Man Kit Sam; Louis, Cynthia; Shihata, Waled; Kraakman, Michael J; Hansen, Jacinta; Masters, Seth L; Hanaoka, Beatriz Y; Nagareddy, Prabhakara R; Lancaster, Graeme I; Wicks, Ian P; Murphy, Andrew J
Abstract: Objectives: Rheumatoid arthritis (RA), an inflammatory joint disorder, independently increases the risk of cardiovascular disease (CVD). IL‐1β contributes to both RA and CVD. We hypothesised that inhibiting IL‐1 signalling with the IL‐1R antagonist, anakinra, would dampen inflammation and promote resolution of atherosclerosis in arthritic mice. Methods: Low‐density lipoprotein receptor (Ldlr)‐deficient mice were fed a Western‐type diet for 14 weeks to develop atherosclerotic plaques. Mice were then switched to a chow diet, promoting lesion regression, and randomised to a control group or into groups where arthritis was induced by passive transfer of K/BxN arthritogenic serum. The arthritic mice were further randomised to vehicle or anakinra. Results: Arthritis impaired atherosclerotic lesion regression when cholesterol was lowered. This was associated with a higher burden of plaque macrophages, likely due to monocytosis, driven by myelopoiesis in the bone marrow and spleen. Interestingly, delayed intervention with anakinra had no effect on arthritis in these mice. However, a significant improvement in atherosclerotic plaque remodelling to a more stable phenotype was observed. This was associated with fewer circulating monocytes, caused by a reduction in splenic extramedullary myelopoiesis. Conclusion: We show that inhibiting IL‐1 signalling in arthritic mice with pre‐existing atherosclerosis promotes lesion remodelling to a more stable phenotype, that is less likely to rupture and cause ischemic events such as myocardial infarction. This suggests that IL‐1R antagonism may suppress CVD complications in patients with RA. Furthermore, inhibiting IL‐1β signalling in other patients with inflammatory diseases that also predispose to CVD may also benefit from anti‐IL‐1 therapy. Abstract : In this study, we found that blocking the interleukin 1 (IL‐1) receptor with anakinra, an IL‐1 receptor antagonist, promoted remodelling of atherosclerotic lesions to a more stable phenotype in mice with inflammatory arthritis. This was associated with reduced myelopoiesis in the spleen and subsequently fewer circulating monocytes that are known to enter atherosclerotic plaques. Our data suggest that in conjunction with standard lipid‐lowering therapy, targeting IL‐1 signalling in cardiovascular comorbidities where IL‐1 is known to play a role may reduce the risk of a cardiovascular event.